INTER-PROFESSIONAL RIVALRY IN NIGERIAN HEALTH SECTOR: A SEARCH FOR A POTENTIAL BEGINNING - Salisu AI; Hauwa IK; Abubakar MA; Ramla F; Mukhtar IG; Nafisa NY (Ntec Specialist, 2020)
Background: Inter-professional rivalry (IPR) in Nigerian health sector has become a common practice for over a decade due to abuse of the existing laws and ethics governing the operations of the professional cadres manning the health institutions in the country. This has led to incessant strikes by the different cadres in the hospitals across the country, thereby affecting the quality of services delivered by all the categories of healthcare staff. This study was aimed at identifying the initial source of the problem by interviewing the students of the Faculty of Basic Medical Sciences of Bayero University Kano (BUK) and that of Yusuf Maitama Sule University (YUMSUK) and those that have passed their examinations and joined the clinical and allied science departments in Bayero University Kano. The Faculty of Basic Medical Sciences is the initial confluent point where all medical and students of allied sciences receive their training together especially in the first and second year of their training. Method: A random sampling method was used to select the subjects. Two hundred questionnaires were distributed but 139 (69.5%) students at various levels of training filled and returned the questionnaire. Results: Females constituted 62 (44.6%), while the male were 77 (55.4%). Those in level 4 and 6 dominated the study with 55 (39.6%) and 41 (29.5%) respectively. Medical students and students of Physiology program constituted 42(30.2%) and 23(16.5%) respectively. Majority of the students 126 (90.6%) chose their respective courses without external influence and 85 (61.2%) believed that their course of study has a supportive role in the health care system. Up to 63 (45.3%) believed there is no superiority among the various courses of study. Of the factors fueling superiority feelings among students, 70 (50.4%) did not provide any reason, while those that believe professional bodies encourage it constituted 40 (28.8%), followed by teachers 11 (7.9%) and students themselves 10 (7.2%). Superiority feelings lead to rivalry among the various programs as opined by 78 (56.1%), chaos in the health sector 26 (18.7%) and poor patients management 12 (8.6%). Majority, 61 (43.9%) believed that rivalry in health sector can be prevented by giving uniform opportunity to all professional groups. Conclusion: It is clear that half of the students interviewed were not aware of superiority feeling among the different programs of study. However, professional bodies rank first among the factors fueling superiority feeling during undergraduate training. Superiority feeling has negative effects on the healthcare system, one of which is rivalry among the healthcare staff and it can be avoided by giving uniform opportunity to different professional groups.